Role of Catalysis in Controlling Air and Water Pollution: A Chemical Perspective - Omkumari (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
One of the most serious and problematic issues in the 21st century is air and water pollution, which creates significant threats to the ecosystem, human health, and the global economy. Industrial effluents, runoff from farms, and waste in urban areas are also to blame for the poor quality of air and water, and in most cases, they require intricate cleaning measures. Physical filtration, chemical precipitation, and adsorption are examples of traditional methods that have been in high demand. However, they are often energy-intensive, expensive, and likely to form secondary pollutants, which impose additional environmental costs. Quite to the contrary, catalysis has also emerged as an attractive and renewable alternative, promising higher potential efficiency, superior selectivity, and lower energy demands. This review broadly applied a chemical approach to detailing how catalytic processes reduce pollution in air and water systems. It covers various types of catalysis, including heterogeneous, homogeneous, biocatalysis, and photocatalysis, as well as the methods used for each, along with the materials that can be employed. The consequences of various innovative features in the handling of wastewater generated by cooking industries, the purification of flue gas, and the testing of pollutants in an environmentally friendly environment are elaborated further in the case studies. Additional common problems (catalyst deactivation, scalability, and economic sustainability) are discussed. In addition, nano-catalysis and engineered enzymes, as well as catalytic design using artificial intelligence, are explored as potential solutions for the next generation of pollution management. Ultimately, as this review underscores, catalysis is not merely a technological Band-Aid, but a groundbreaking pillar of sustainable development that aligns with the principles of green chemistry, offering a path to healthier and more sustainable ecosystems worldwide.